Social support status and associated factors among people living with HIV/AIDS in Kunming city, China - Yi Li; Xiao-Wen Zhang; Bin Liao; Jun Liang; Wen-Jie He; Jun Liu; Yao Yang; Yun-Hai Zhang; Tao Ma; Jing-Ying Wang (BMC, 2021)
Abstract Background People living with HIV/AIDS not only require effective treatment for the alleviation of physical discomfort but also require social support to help them address difficulties in life and relieve their psychological anxiety and uneasiness. The social support network is of tremendous importance in helping people living with HIV/AIDS maintain good physical and mental health. This study aims to analyse the social support status among people living with HIV/AIDS in Kunming and explore associated factors. Method The Social Support Rating Scale (SSRS) was used, and a questionnaire survey was conducted using convenience sampling to select people living with HIV/AIDS from 14 counties of Kunming. It collected information on general demographic information and social support status. Univariate and multivariate linear regression models were used to explore the associated factors. Results A total of 990 valid questionnaires were completed. Data from all participants were analysed. Univariate analysis suggested that the factors associated with social support may include marital status, monthly income, and antiretroviral therapy. On the other hand, factors including monthly income and antiretroviral therapy accounted for the social support total score in the multivariate analysis. Conclusion Social support among people living with HIV/AIDS in Kunming was generally low. This study identified a number of factors associated with social support among people living with HIV/AIDS. Based on our findings, appropriate interventions should be introduced to provide social support for those living with HIV/AIDS.